Saints and virtues - Hawley, John Stratton (Comparative studies in religion and society, 1987)
The saint as exemplar in late antiquity / Peter Brown -- A theater of virtue : the exemplary world of St. Francis of Assisi / Hester Goodenough Gelber -- Prophet and saint : the two exemplars of Islam / William M. Brinner -- Morality beyond morality in the lives of three Hindu saints / John Stratton Hawley -- the Confucian sage / Tu Wei-ming -- Sainthood on the periphery : the case of Judaism / Robert L. Cohn -- The Buddhist arahant / Stanley J. Tambiah -- Saints and virtue in African Islam / Lamin Sanneh -- Alourdes : a case study of moral leadership in Hatian Vodou / Karen McCarthy Brown -- Sathya Sai Baba's saintly play / Lawrence A. Babb -- Saint Gandhi / Mark Juergensmeyer -- Conclusion : after sainthood? / John A. Coleman